REGIONAL DIVERSIFICATION OF TRITICALE PRODUCTION IN POLAND - Bogusława JAŚKIEWICZ (Journal of Central European Agriculture, 2009)
The sources for regional diversifi cation analysis of the triticale production were statistical GUS data from 2006-2007, accessed according to the voivodeship. The cluster analysis method was used to isolate fi ve groups of voivodeships, which differed in triticale production (fi g. 1) Triticale cultivation is concentrated mainly in Wielkopolska and Kujawy and in central and eastern parts of the country. The amount of triticale cultivation in regions was associated with the foodstuff production for pig and poultry populations. It was witnessed in the eastern part of the country, where the considerable share of the triticale was stated in the structure of cropland.